Leak-Free Group Signatures with Immediate Revocation - DING, Xuhua (Institutional Knowledge at Singapore Management University, 2004)
Group signatures are an interesting and appealing cryptographic construct with many promising potential applications. This work is motivated by attractive features of group signatures, particularly, their potential to serve as foundation for anonymous credential systems. We re-examine the entire notion of group signatures from a systems perspective and identify two new security requirements: leak-freedom and immediate-revocation, which are crucial for a large class of applications. We then present a new group signature scheme that achieves all identi.ed properties. Our scheme is based on the so-called systems architecture approach. It is more ef.cient than the state-of-the-art and facilitates easy implementation. Moreover, it reflects the wellknown separation-of-duty principle. Another benefit of our scheme is the obviated reliance on underlying anonymous communication channels, which are necessary in previous schemes.